Role of the hormonal system "Vitamin D/Vitamin D receptors" in the formation of some pregnancy complications - G. S. Manasova; A. G. Andrievsky; N. V. Didenkul; I. V. Shpak; M. I. Turchyn; N. V. Kuzmin (Publishing House TRILIST, 2020)
Introduction. The hormonal system "vitamin D/vitamin D receptors" (VD/VDR) is involved in the regulation of numerous physiological processes. VD lack or deficiency is associated with a number of different diseases, including pregnancy complications. Purpose of the study: to determine VD status and its effect on the course of the gestational process in women from the southern region of Ukraine. Materials and methods. 459 women were examined, 318 (69.3%) of them were the main group and 141 (30.7%) were the comparison group. In addition to standard general clinical examinations, ELISA on a COBAS Integra 400 Plus analyzer (Roche Diagnostics, Switzerland) the VD level was determined in the blood. Results and discussion. 49.9% of the pregnant women in the main group had insufficient VD level (25.45 ± 4.63 ng/ml), in 19.4% it corresponded to a deficit (15.28 ± 4.78 ng/ml). VD concentration in the comparison group was 43.38 ± 9.67 ng/ml (p <0.01). Significantly more frequent pregnancy complications in the main group were threatening abortion (45.6% VS 9.9%; F = 0.00001; p <0.01), preeclampsia (13.5% VS 2.8%; F = 0.0093; p <0, 05), placental dysfunction (32% VS 7%; F = 0.00001; p <0.01), vaginal dysbiosis (64.4% VS 18.4%; F = 0.00001; p <0.01), pregnant anemia (43.7% VS 20.6%; F = 0.0008; p <0.01) and signs of inflammation of the amniotic membranes (38.3% VS 13.4%). Syndrome of intrauterine growth retardation diagnosed in 9% women in the main group; in the comparison group none case was noted. Conclusion. 70% of pregnant women in Odesa region have a lack or deficiency of VD. Pregnancy course is characterized by a significantly greater frequency of preeclampsia (4.8 times more often), placental dysfunction (4.5 times), threat of miscarriage (4.6 times more often), intrauterine infection (2.8 times more often), gestational anemia (2.5 times more). It seems promising to conduct further research on the possibility of preventing complications of the gestational process by correcting VD status.